The craft of structure in R. Ellison's invisible man - BOUGHERARA, Khemissi (Journal of Human Sciences, 2006)
Ellison’s advocacy of art against sociology and ideology is well-known. In his only novel, Invisible Man, he demonstrates that Negro writers are perfectly capable mastering the Euro-American literary tradition, and that great works of art with universal implications can be worked out of the raw material of Black life. The structure of the novel portrays a black man’s renewed attempt to establish his human individuality, first within and against his Black community, and within and against American society.